Evagrius Ponticus and the Eastern Monastic Tradition on the Intellect and the Passions - Stewart, Columba (Modern theology, 2011)
Evagrius Ponticus (c. 345-399) combined the resources of Hellenistic philosophy, the theologies of Origen and the Cappadocians, and Egyptian monastic practice to create a comprehensive view of spiritual development, within which he placed a sophisticated study of the human passions. His main tools in this study were an adapted version of Platonic tripartite anthropology and his own system of eight "generic thoughts." Freedom from control by irrational passions would allow a monk to gain deeper insight into the meaning of Scripture, experience communion with God in "pure prayer," and love other people in freedom. Evagrius' influence on later eastern and western Christian traditions was profound, though often obscured by his controversial reputation.